Alternative least-squares scaling algorithm (ALESSA) for wireless sensor networks localization - Lucas, Lou Bryan Español (2008)
Current localization schemes for Wireless Sensor Networks such as GPS, APS, SDP, ALS, MDS-MAP and its variants are limited by cost, accuracy, minimum number of anchor nodes, and computational complexity. The algorithms based on Multidimensional Scaling (MDS), which can be used with simple hardware, only require a small percentage of anchor nodes and can provide higher accuracy than other schemes. In this research, we propose the use of Publico's Alternative Least-Squares Scaling Algorithm (ALESSA), another type of MDS algorithm, for the localization problem. Publico's work on ALESSA was motivated by the mean form estimation problem, and ALESSA has not yet been applied to localization. ALESSA uses an iterative approach to solve for the coordinates of discrete points using noisy inter-point distance measurements. The performance of ALESSA is compared with that of Ordinal MDS, another iterative MDS algorithm, and ALESSA shows better performance in terms of processing time and localization accuracy. Coordinate System Registration (CSR) is also applied to mitigate flip ambiguity, a problem with MDS algorithms which introduces large errors in location estimates, even though accurate relative localization may be achieved. We have also shown that the number of anchor nodes has a more significant effect on the likelihood of flip ambiguity than the amount of noise in the inter-point distance measurements. ALESSA and CSR are combines in a localization scheme, and performance evaluation shows significantly accurate localization even with very noisy inter-point distance measurements and few anchor nodes. A hardware testbed is also constructed, where the performance of the localization scheme is evaluated.
"April 2008."
Thesis (M.S. Electrical Engineering)--University of the Philippines Diliman.
Keywords: Sensor networks; Wireless sensor networks; Wireless LANs; Wireless communication systems; Sensor networks